PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN AKUNTANSI SUMBER DAYA MANUSIA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2013 - Cristy, Nia; Tanjung, Amries Rusli; Darlis, Edfan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to know the effect of firm’s characteristics to human resource accounting disclosure (HRAD). This HRAD is measured uses 16 index of Mamun (2009) study. The population in this study is manufacturing company that listing in Indonesia Stock Exchange in 2011-2013. The sampling technique using purposive sampling method so from 148 companies only 60 that appropriate criteria with total observation 180 companies during 3 years. The data of this research is using secondary data with collecting data method by downloading annual report on web BEI. Analysis data method that is used in this study is multiple linear regression with helping of software SPSS 17.0 version.The results of this study show that firm’s age and product diversification have effect on HRAD with significant rate 5% (b3=0.024, b4=0.000). While firm’s size and profitability have no effect on HRAD with significant rate 5% (b1=0.425, b2=0.501). The R-square value is equal to 0.149, which means 14.9% of independent variables in this study could affect the dependent variable. While remaining 85.1% is explained by other variables that are not included in this study.Keywords: Firm’s Size, Profitability, Age, Product Diversification, and Human Resource Accounting Disclosure (HRAD)